CLINICAL SIGNIFICANCE OF ANTENALHEMOGLOBIN TYPES DETERMINATION IN PROGNOSIS OF EARLY ADAPTATION IN PREMATUPE NEWBORNS - L.A. Bakhmutova; D.M Nikulina; Yu.A. Kriventsev (Вопросы современной педиатрии, 2009)
(Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(2):120-122)